Evaluation of front line Demonstration on Mustard Crop in Bundelkhand Zone - Singh, Anil Kumar; Chauhan, Rajeev; Rikhari, Y.C.; Kumar, Puneet (Indian Journal of Extension Education, 2020)
Krishi Vigyan Kendra, Datia, Madhya Pradesh conducted 517 demonstrations on mustard varieties RVM-2 and NRCHB-101 during five consecutive years from 2014-15 to 2019-20 at farmers’ field in Datia district to find out the worth of the improved technology. The parameters like technological impact, economical impact and extension gap were analyzed and feasibility of demonstrated technologies at grass root levels was assessed. The results of five years study revealed that the yield under demonstration plots was 19.79 q/ha as compared to 15.77q/ha in traditional farmer practices plots. This additional yield of 4.02q/ ha and the increase in average mustard productivity by 25.24 per cent may contribute to present oilseed requirement on national basis. The average of technology gap, extension gap and technology index were found to be 287.00 kg/ha, 401.75 kg/ha and 12.70 per cent respectively. An additional investments of Rs.1633 per ha coupled with scientific monitoring of demonstrations and non-monetary factors resulted in additional net return of Rs.12884 per ha. Fluctuating sale price of mustard during different years influenced the economic returns per unit area. On five years overall average basis incremental benefit cost ratio was found as 3.28. The results clearly indicate the positive effects of FLDs over the existing practices.
Keywords: Benefit cost ratio; Extension gap; Technology gap; Technology index